Risk of pulp damage may increase due to intrachamber temperature during the usage of prophylaxis cup without paste (Annals of Medical Research, 2021)
Aim: The aim was to measure in vitro pulp temperature increase over physiologic temperature during usage of different prophylaxis regimes at two different application pressures.Material and Methods: The aim was to measure in vitro pulp temperature increase over physiologic temperature during usage of different prophylaxis regimes at two different application pressures.Results: The aim was to measure in vitro pulp temperature increase over physiologic temperature during usage of different prophylaxis regimes at two different application pressures. Conclusion: Within the limitations of this in vitro study following conclusion can be drawn: Prophylaxis cups without paste generated the highest intrachamber temperature thus, the risk of pulp damage might be increased during its usage. Naturel-bristled prophy brushes generated the lowest intrachamber temperature. Vigorous application pressure increased the intrachamber temperature.
Keywords: Dental prophylaxis; pulp; prophy cups; tooth-polishing; pulp damage